Signaling by wingless in Drosophila. - Klingensmith, J.; Nusse, R. (Developmental Biology, 1994)
Wingless, a member of the Wnt gene family, is an essential gene for segmentation in Drosophila, and is also involved in many other patterning events. The gene encodes a secreted protein that can regulate gene expression in adjacent cells. Recently, significant progress has been made in elucidating the signal transduction pathway of wingless, mainly by genetic experiments but increasingly also at the biochemical level. While many components of wingless signaling, in particular a receptor, remain to be identified, our current understanding of wingless pathway is more advanced than that of other Wnt genes. We will give an overview of the various roles of wingless in development, and we will then summarize the wingless signaling pathway as it has emerged from genetic and biochemical studies. Where appropriate, wingless signaling will be compared to the activity of vertebrate Wnt proteins.